Valorization of agricultural waste for biogas based circular economy in India: A research outlook. (May 2020) - Kapoor, Rimika; Ghosh, Pooja; Kumar, Madan; Sengupta, Subhanjan; Gupta, Asmita; Kumar, Smita S.; Vijay, Vandit; Kumar, Vivek; Kumar Vijay, Virendra; Pant, Deepak
Graphical abstract: Highlights: Need for agri-waste derived biogas based circular economy has been discussed. Anaerobic digestion is a promising technology for agri-waste valorisation in India. Valorization of products of anaerobic digestion for circular economy has been discussed. Barriers in supply chain and technical knowledge impede growth of circular economy. Requirement of efficient implementation of policy and regulatory framework exists. Abstract: Environmental deterioration and the need for energy security are intrinsic problems linked with the linear economy based on fossil fuels. Recently, a transformation to a sustainable circular bio-economy is being experienced where biomass waste is being valorized for energy production as well as minimization of waste and greenhouse gas emissions. The agricultural waste, generated in vast quantities in India is a prospective feedstock for biogas production. Agri-waste to biogas based circular economy requires an integration of agri-waste management, biogas production and utilization and policy support. This paper comprehensively discusses the potential of biogas production from agricultural waste, its upgradation and utilization along with the government initiatives, policy regulations. In addition, barriers that impede the development of an efficient agri-waste to biogas based circular economy, and the future research opportunities to meet the growing needs for agri-waste management, energy production and climate change mitigation are discussed.